Informative content of clinical symptoms of acute appendicitis in different terms of pregnancy. - A. B. Kutovoy; I. I. Petrashenkо (Medičnì Perspektivi)
With the purpose to evaluate diagnostic efficacy of some clinical symptoms of acute appendicitis 75 women in different terms of pregnancy were examined. Informative content of such symptoms as Kocher- Volkovich, Rovsing, Bartomje - Michelson, Sitkovsky, Gabay, Brendo, Michelson, Ivanov was studied. Pain syndrome was fixed in all examined women. Pain localization was various and depended on the pregnancy term. During the I trimester of pregnancy the most often pain was manifestated in epigastrium and right lower quadrant, rarely in other abdomen regions. In the II trimester in majority of cases pain occurred in right lower quadrant. During III trimester pain prevailed in right upper quadrant of abdomen. Analyzing informative component of researching symptoms there was noted significant decrease (р<0,05; р<0,01; р<0,001) of their diagnostic value with growth of pregnancy term. Therefore Kocher – Volkovich and Rovsing symptoms were the most informative in the I trimester of pregnancy. Diagnostic efficacy of Brendo(67,3%), Michelson(55,7%),  Ivanov(59,6%) symptoms was higher than that of Kocher – Volkovich (36,5%),  Rovsing (28,8%), Sitkovsky (51,9%), Bartomje – Michelson (55,7%) symptoms, their value was diminishing together with increase of pregnancy terms.